Needle electromyography of the frontalis muscle in patients with amyotrophic lateral sclerosis. Issue 6 (26th September 2016) - Pan, Hua; Jian, Fan; Lin, Jinxi; Chen, Na; Zhang, Zaiqiang; Wang, Yongjun; Cui, Liying; Kimura, Jun
ABSTRACT: Introduction: We sought to determine which muscles to choose for better assessment of the craniobulbar region in establishing the diagnosis of amyotrophic lateral sclerosis (ALS). Methods: We studied the frontalis muscle in 83 controls and compared it with the tongue, sternocleidomastoid (SCM), and trapezius muscles in 105 definite or probable ALS patients (54 bulbar, 51 nonbulbar). Results: More patients achieved complete relaxation of the frontalis muscle than the tongue or SCM. Motor unit potentials were of longer duration and higher amplitude in ALS patients than in controls ( P < 0.05). The frontalis had the same frequency of spontaneous potentials as the tongue, SCM, and trapezius muscles in bulbar ALS patients, but fewer than in the trapezius in nonbulbar patients. Conclusions: Examining the frontalis provides useful information in establishing the diagnosis of ALS by identifying clinically evident or subclinical abnormalities in the craniobulbar region. Muscle Nerve 54 : 1093–1096, 2016